Structural stability of cobalt ferromagnetic nanowires embedded in CeO2/SrTiO3(0 0 1) after oxidative/reductive annealing. (14th May 2015) - Novikova, A; Fonda, E; Dumont, Y; Zheng, Y; Demaille, D; Vidal, F
Abstract: We studied the modifications induced by oxidative annealing and followed by high vacuum reductive annealing on the structure of fcc Co nanowires; the nanowires are obtained by alternate pulsed laser deposition (PLD) from CoO and CeO2 targets on SrTiO3 (0 0 1). Their structural and magnetic properties were observed by means of x-ray absorption spectroscopy and vibrating sample magnetometry, respectively. We correlated the structure modifications with the magnetic properties: after a complete cycle the local structure is restored as well as the saturation magnetization, though the magnetic loops of the cycled sample differ in shape suggesting that the treatment modifies the magnetic microstructure and that two populations of magnetic objects exist at the end. The intermediate oxidized sample has been studied in detail: oxidation induces the formation of an oxygen defective nano-CoO structure that exhibits a short Co-O bond (2.03 Å).